Field evaluation of the performance of seven Antigen Rapid diagnostic tests for the diagnosis of SARs-CoV-2 virus infection in Uganda. - Josephine Bwogi; Tom Lutalo; Phionah Tushabe; Henry Bukenya; James Peter Eliku; Isaac Ssewanyana; Susan Nabadda; Christopher Nsereko; Matthew Cotten; Robert Downing; Julius Lutwama; Pontiano Kaleebu; et al. (PLoS ONE)
Objective The objective of this study was to evaluate the performance of seven antigen rapid diagnostic tests (Ag RDTs) in a clinical setting to identify those that could be recommended for use in the diagnosis of SARS-CoV-2 infection in Uganda. Methods This was a cross-sectional prospective study. Nasopharyngeal swabs were collected consecutively from COVID-19 PCR positive and COVID-19 PCR negative participants at isolation centers and points of entry, and tested with the SARS-CoV-2 Ag RDTs. Test sensitivity and specificity were generated by comparing results against qRT-PCR results (Berlin Protocol) at a cycle threshold (Ct) cut-off of ≤39. Sensitivity was also calculated at Ct cut-offs ≤29 and ≤33. Results None of the Ag RDTs had a sensitivity of ≥80% at Ct cut-off values ≤33 and ≤39. Two kits, Panbio™ COVID-19 Ag and VivaDiag™ SARS-CoV-2 Ag had a sensitivity of ≥80% at a Ct cut-off value of ≤29. Four kits: BIOCREDIT COVID -19 Ag, COVID-19 Ag Respi-Strip, MEDsan® SARS-CoV-2 Antigen Rapid Test and Panbio™ COVID-19 Ag Rapid Test had a specificity of ≥97%. Conclusions This evaluation identified one Ag RDT, Panbio™ COVID-19 Ag with a performance at high viral load (Ct value ≤29) reaching that recommended by WHO. This kit was recommended for screening of patients with COVID -19-like symptoms presenting at health facilities.